Increased incidence of urinary tract infections caused by Enterococcus in COVID-19 patients of the Clinical Center of Vojvodina - Smieško, Gordana; Baroš Brkljača, Marija; Banović, Pavle Z (PONS - medicinski časopis, 2022)
Objective: To investigate the frequency of isolates of various uropathogens in patients of COVID19 Hospital "Mišeluk" in comparison with patients from the non-COVID19 zone of the Clinical Center of Vojvodina (KCV).Methods: For the purpose of this study, information was collected on urine isolates sent from COVID19 hospital and non-COVID19 zones of the Clinical Center of Vojvodina in a three-month period, with samples from non-COVID19 zone KCV served as controls.Results: Of the 449 patients from COVID19 Hospital, the most common causative agents of intrahospital urinary infection (IUI) were members of the genus Enterococcus, (216/449; 48.10%), who in most cases caused IUI in women (127/216; 58.79%). The second most common causative agent of IUT in COVID19 is Klebsiella pneumoniae (85/449; 18.93%). Of the 913 patients from the non-COVID19 KCV clinic, the most common cause of IUI was Escherichia coli (249/913; 27.27%), predominantly in women (199/249; 79.91%, (χ2 (1) = 49,042). p
Keywords: urine; COVID19; Vojvodina; Enterococcus; Escherichia coli